Simple IoT-Based Home Security System Using ESP32 and Blynk - Fikri, Abdul (Talenta Publisher, 2025)
Advances in Internet of Things (IoT) technology have brought about various innovations in home security systems. This research aims to design and implement an IoT-based home security system integrated with the ESP32, the KY-037 sound sensor, and the HC-SR501 PIR motion sensor. This system is capable of detecting suspicious movement or sounds around the home door and then sending real-time notifications to the Blynk app on the user's smartphone. The method used was the development of an ESP32-based prototype connected to the internet to transmit sensor data. Test results show that the system can provide notifications with a response time of less than 2 seconds. This system is easy to implement, energy efficient, and suitable for household use. This research demonstrates the great potential of IoT in improving security with affordable costs and high flexibility. The study also highlights the importance of sensor threshold testing to improve detection accuracy. Further developments could include integration with IP cameras and facial recognition systems.